Fabrication and characterization of a novel nanofiltration membrane by the interfacial polymerization of 1, 4-diaminocyclohexane (DCH) and trimesoyl chloride (TMC). Issue 51 (5th June 2015) - Chen, Gui-E.; Liu, Yan-Jun; Xu, Zhen-Liang; Tang, Yong-Jian; Huang, Hui-Hong; Sun, Li
<x xml:space="preserve">Abstract</x> A novel thin-film composite polyamide membrane for nanofiltration is prepared, and the addition of sodium N-cyclohexylsulfamate is found to have a significant influence on its performance.